Assessment of Nurses' Performance in Caring for Cancer Patients in Kirkuk City: a Cross Sectional Study - Hamdiya Muhammed; Yousif Salih (Health & Medical Sciences, 2025)
Cancer is considered one of the major issues in the twenty-first century. It's one of the leading causes of death and a barrier to life expectancy, globally. Its burden expected to increase worldwide from 2020 and throughout the first half of the 21st century. Nurses as one of the medical team are considered at the frontline in mitigating this increasing, through their contributions in patients care with their diversity of care roles and responsibilities in cancer care. This study aimed to assess oncology nurses level of performance in cancer care in Kirkuk City. Methods, a descriptive (cross sectional) design conducted at Oncology and Hematology Center in Kirkuk City, Iraq. An observational checklist used to collect data of 81 nurse in the time line between February 15th, 2025 to March 27th,2025. Results, nurses showed an overall weak adherence to cancer care protocols in general(PGMS=24.28%), where nurses scored low levels in both the " Supportive and psychological nursing care" and "Nursing care throughout chemotherapy treatments" with a Percentile Grand/Global Mean of Score (PGMS) of 8.80%,and 8.82% respectively; while they showed a moderate level in regard to "Nursing care prior to handling chemotherapeutic agents", (PGMS=56.02%). No relationship accounted between Nurses' performance level and the studied respondent's socio-demographics(age, educational background, and years of experience), since no significant a contingency coefficients are accounted at P>0.05, except in regard of gender variable (CC = 0.249) at the value of P < 0.05,showing a better advantage for male over females. Conclusion: The findings indicates a weak adherence to the protocols regarding cancer patient care, indicating the need for further focus on the provision of continuous trainings. Furthermore, the findings of the study allow us to make the assumption that nurses' age , educational qualification, and experience doesn't necessarily have to play a significant role in the evaluation of nurse competence and quality of nursing care provided in all of the environments.